Balanced Scorecard BALANCED SCORECARD UNTUK MENGUKUR KINERJA KOPERASI PARIWISATA (KOPARI) “SAPTA PESONA” KABUPATEN BANJARNEGARA - Kasih, Veilla Anggoro; Hefiana, Fera; Wiratno, Adi (Medikonis, 2024)
This study aims to measure the financial and non-financial performance of the Tourism Cooperative (KOPARI) "Sapta Pesona" Banjarnegara Regency comprehensively using the balanced scorecard method. This balanced scorecard method helps measure and evaluate the performance of cooperatives from the perspectives of finance, members, internal business processes, and learning and growth. The research is a qualitative study with data collection techniques using questionnaires, observation, and document analysis. The results showed that the performance of the cooperative as measured from a financial perspective using the profitability ratio was in the good category, the poor category in the liquidity ratio, and the very good category in the solvency ratio. Meanwhile, based on the measurement of the customer perspective, internal business process perspective, and learning and growth perspective, KOPARI Sapta Pesona Banjarnegara Regency is included in the good category. Thus the performance of KOPARI Sapta Pesona Banjarnegara which is reviewed using a non-financial perspective is good, and the financial perspective still needs to be improved and paid attention to. Keywords: Balance Scorecard, Cooperative, Financial Perspective